Use the identity (x + a)(x + b) = x2 + (a + b)x + ab to find the following products.
(i) (x + 3) (x + 7)
Use the identity (x + a)(x + b) = x2 + (a + b)x + ab to find the following products.
(4x + 5) (4x + 1)
Use the identity (x + a)(x + b) = x2 + (a + b)x + ab to find the following products.
(4x - 5) (4x - 1)
Use the identity (x + a)(x + b) = x2 + (a + b)x + ab to find the following products.
(4x + 5) (4x - 1)
Use the identity (x + a)(x + b) = x2 + (a + b)x + ab to find the following products.
(2x +5y) (2x + 3y)
Use the identity (x + a)(x + b) = x2 + (a + b)x + ab to find the following products.
(2a2 + 9) (2a2 + 5)
(2a2 + 9) (2a2 + 5)= [2a2] + (9 + 5)2a2 + 9 x 5
= 4a4 + 14 x 2a2 + 45
= 4a4 + 28a2 + 45
Use the identity (x + a)(x + b) = x2 + (a + b)x + ab to find the following products.
(xyz - 4) (xyz - 2)